#### Question

Solve the following quadratic equations by factorization: \[\sqrt{3} x^2 - 2\sqrt{2}x - 2\sqrt{3} = 0\]

#### Solution

\[\sqrt{3} x^2 - 2\sqrt{2}x - 2\sqrt{3} = 0\]

\[ \Rightarrow \sqrt{3} x^2 - 3\sqrt{2}x + \sqrt{2}x - 2\sqrt{3} = 0\]

\[ \Rightarrow \sqrt{3}x\left( x - \sqrt{6} \right) + \sqrt{2}\left( x - \sqrt{6} \right) = 0\]

\[ \Rightarrow \left( \sqrt{3}x + \sqrt{2} \right)\left( x - \sqrt{6} \right) = 0\]

\[ \Rightarrow \sqrt{3}x + \sqrt{2} = 0 \text { or } x - \sqrt{6} = 0\]

\[ \Rightarrow x = - \sqrt{\frac{2}{3}} \text { or } x = \sqrt{6}\]

Hence, the factors are \[\sqrt{6}\] and \[- \sqrt{\frac{2}{3}}\].

Is there an error in this question or solution?

#### APPEARS IN

Solution Solve the Following Quadratic Equations by Factorization: Concept: Solutions of Quadratic Equations by Factorization.